Rosaline Palmer takes the cake - Hall, Alexis J. (Forever, 2021)
"Rosaline Palmer is just barely holding her life together. Her paycheck might as well be parchment paper, her house is falling apart, and help from her parents is always served with a generous slice of disappointment and judgment. And the cherry on top? Now her daughter's school is charging all sorts of outlandish extra fees for trips that Rosaline can't afford. But where there's a whisk there's a way. . . and Rosaline has just landed a place on the nation's favorite baking show. Winning the prize money could change everything, but more than collapsing trifles stand between Rosaline and sweet, sweet victory. Charming and suave Alain Pope is just the type of person her parents planned for her to marry, and better yet, her fellow contestant is doing his best to sweep her off her feet. Yet while he says and bakes all the right things, it's friendly, down-to-earth electrician Harry Dobson who Rosaline finds as tempting as a midnight ice-cream sundae with salted caramel . . . and just as hard to resist. But as the competition -- and the ovens -- heat up, Rosaline starts to realize the most delicious recipes come about when you don't follow the recipe"--